2021
DOI: 10.7759/cureus.12628
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Positioning for Robotic Prostatectomy: Results From a Survey of the Endourological Society

Abstract: Purpose: most robot-assisted laparoscopic prostatectomies (RALP) are performed with the patient in lithotomy, carrying risks of positioning-related complications. Newer robot models have allowed for supine positioning, potentially avoiding these pitfalls. We gauged the current sentiment on patient positioning among surgeons who perform robot-assisted surgery. Methods: we surveyed members of the Endourological Society regarding their practice settings and their opinions on positioning for robot-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Close communication between the surgeon and anesthetist ensures optimal patient positioning for operative efficiency. The most common positioning for RARP is lithotomy with Trendelenburg with the docking cart between the legs or at the patients' side [29].…”
Section: Patient Positioning and Room Set Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Close communication between the surgeon and anesthetist ensures optimal patient positioning for operative efficiency. The most common positioning for RARP is lithotomy with Trendelenburg with the docking cart between the legs or at the patients' side [29].…”
Section: Patient Positioning and Room Set Upmentioning
confidence: 99%
“…Lithotomy positioning and any exaggerated stretch or compression caused by the tilting into Trendelenburg position is associated with a significant risk of lower limb neuropraxia [29]. The most common lower limb neuropathies associated with lithotomy procedures are common perineal and sciatic [32].…”
Section: Neuropraxia and Compartment Syndromesmentioning
confidence: 99%
“…The safety and feasibility of radical prostatectomy in supine position is now well established and has been shown to shorten and simplify the setup time, along with significantly reduced position related injuries 3 . A recent survey of urologists showed that the majority (75%) of the respondents were performing radical prostatectomy in the lithotomy position and only 3% used the split leg position and 22% used the supine position 4 . Surgical team familiarity was the commonest reason for continuing with the lithotomy position.…”
mentioning
confidence: 99%